PENGARUH AKTIVITAS, SOLVABILITAS, DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN - Averina, Gracia; Susanto, Liana (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence about the effect of activity, solvency and liquidity on profitability in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The number of samples in this study were 48 property and real estate companies selected by purposive sampling method. The research data were analysed using multiple linear regression analysis techniques which were processed with SPSS ver.21 software. The results of this study indicate that activity have a significant and positive effect on profitability. Solvency activity have a significant and negative effect on profitability. Liquidity have no significant effect on profitability. The implication of this research is the need to increase activity value while maintaining a certain solvency level to increase the company's profitability which will increase the firm's value and provide a good signal for investors.